Diagnosis cepat infeksi saluran kemih dengan menghitung jumlah leukosituria pada urinalisis metode flowcytometry sysmex UX-2000 dengan baku emas kultur urin di RSUP Sanglah Denpasar - Mega Pratistha, Fernanda Savitri; Sudhana, I Wayan; Adnyana, I Wayan Losen (E-Jurnal Medika Udayana, 2018)
Urinary Tract Infection (UTI) is a bacterial infection of the urinary tract, one of the most common infectious diseases in developing countries. UTI menempati peringkat kedua, after surgical wound infection as a nosocomial infection. Urine culture is a gold standard that is often used to confirming the UTI diagnosis, but has some limitation that is expensive and time consuming to get results. The urine analyzer by flowcytometry method can be used because it is more practical and faster to diagnosed UTI. The aim of the study is to determine the sensitivity, specificity, and accuracy on the automatic urine analyzer by flowcytometry of Sysmex UX-2000. This study is a diagnostic test. Data used in this study is patient who is diagnosed UTI clinically in Sanglah Central Hospital from 2016 until 2017. Subject of the study were 100 people with aged 2 years till up to 65 years. The statistical analysis computer program SPSS.23 and ROC curve to get the most optimal cut off point for leukocytes count then calculated sensitivity, specificity, positif predictive value, negative predictive value and accuracy. Based on Receiver operating characteristic (ROC) curve analysis showed an area under the curve (AUC) for leukocytes count is 0.846 and applying cut off point ?52.8/mL has a sensitivity 82,3%, specificity 76,3%, positive predictive value 85% negative predictive value 72.5% and accuracy 80%. Automatic Urine Analyzer by Flowcytometry Method has high Sensitivity, Specificity, and Accuracy so that it can be applied to help diagnosed UTI. Keywords : Urinary Tract Infection, flowcytometry urine analyzer, Urine Culture